2012
DOI: 10.1002/j.2161-1874.2012.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Counseling Students' Attitudes Regarding Substance Abuse and Treatment

Abstract: Undergraduate counselors‐in‐training completed the Substance Abuse Attitude Survey, which measures treatment intervention, treatment optimism, and nonstereotypical attitudes. Treatment optimism was positively correlated with nonstereotypical attitudes and treatment intervention. Results indicated that treatment intervention and nonstereotypical attitudes must be addressed in addiction counseling courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Furthermore, it would be important to consider if and how instructors' background could account for some the content and delivery method variability that were revealed in previous studies on addiction counseling education. Chasek et al (2012), Iarussi et al (2013), and Lee (2014) indicated that there are significant inconsistencies in the course content and delivery methods in addiction counseling classes. Considering the apparent level of influence instructors' background could have on shaping the overall course goals, one would expected that these factors, at least partially, affect content structure and delivery methods in addiction counseling classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it would be important to consider if and how instructors' background could account for some the content and delivery method variability that were revealed in previous studies on addiction counseling education. Chasek et al (2012), Iarussi et al (2013), and Lee (2014) indicated that there are significant inconsistencies in the course content and delivery methods in addiction counseling classes. Considering the apparent level of influence instructors' background could have on shaping the overall course goals, one would expected that these factors, at least partially, affect content structure and delivery methods in addiction counseling classes.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of quality preparation of professional counselors falls on counselor educators and counselor education programs, which must ensure counselors‐in‐training receive appropriate learning opportunities in treating clients with addictive disorders. Counselor education programs must prepare future counselors to understand the depth and impact of addictive disorders, implement culturally relevant interventions, and recognize and treat multifaceted dually diagnosed clients (Chasek et al, 2012; Harrawood et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, practitioners who have not experienced addiction have been found to be less empathic and to utilize a narrower range of treatment techniques in their work with people with substance use disorders (Bylsma, 2010;Stoffelmayr et al, 1998). Researchers have reported that some helping professionals negatively stigmatized clients with substance addiction, viewing use and relapse as a choice or moral failing (Chasek, Jorgensen & Maxon, 2012;Room, 2009; Van, Eliason, Freudenberg, & Barnes, 2009). These assumptions may lead to a lack of understanding and support and even to inferiorizing, disrespectful interactions (Ballon & Skinner, 2008;Hayes et al, 2004).…”
mentioning
confidence: 99%